Effect of Business Ethics and Professional Ethics to the Perception of Students - Kusworo, Ahmad Dzulfikri Budi (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to determine whether there are differences in business ethics and professional ethics to the perception of students. This research was conducted at one of universities in Indonesia. The type of research used by the authors was survey research. Data collection technique is done by distributing questionnaires. To earn value that supports the purpose of this study conducted a t-test to determine whether there are differences about business ethics and professional ethics to the perception of students and college students. Based on the difference of business ethics between perceptions of students it is concluded that there is a significant difference of business ethics between student and student perception. Based on the result of difference about professional ethics between student perception and student perception can be concluded there is significant difference about professional ethics between student and student perception.